Cobalt-Catalyzed, Aminoquinoline-Directed Coupling of sp(2) C–H Bonds with Alkenes - Grigorjeva, Liene (American Chemical Society, 2014)
[Image: see text] A method for cobalt-catalyzed, aminoquinoline-directed ortho-functionalization of sp(2) C–H bonds with alkenes has been developed. Reactions proceed at room temperature in trifluoroethanol solvent, use oxygen from air as an oxidant, and require Mn(OAc)(3) as a cocatalyst. Benzoic, heteroaromatic, and acrylic acid aminoquinoline amides react with ethylene as well as mono- and disubstituted alkenes affording products in good yields. Excellent functional group tolerance is observed; halogen, nitro, ether, and unprotected alcohol functionalities are compatible with the reaction conditions.